THE JUSTIFICATION OF THE LAYING SCHEMEOF CONCRETE SLEEPERS INSTEAD OF UNUSABLE WOOD - Kalenyk, K. L. (Science and Transport Progress, 2008)
In the given paper the possibility of occurrence of resonant effects in the rail structure was analyzed. Such phenomena impossibility is theoretically proved under existing structure of the rail track and the motion speeds of the rolling stock permitted by the UZ.